2020
DOI: 10.1177/2050640619889763
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of systemic serious viral infections in patients with inflammatory bowel disease associates with active disease and use of thiopurines

Abstract: Background The magnitude and drivers of the risk of serious viral infections in Inflammatory Bowel diseases (IBD) are unclear. Objective The objective of this study was to assess the incidence and risk factors for systemic serious viral infections in IBD patients. Methods Using MICISTA, a database detailing prospective characteristics and complications of IBD, we identified patients that were followed for IBD in 2005–2014 outside the context of organ transplantation, HIV infection or chronic viral hepatitis. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 35 publications
4
87
1
10
Order By: Relevance
“…14 In a large study, thiopurines but not biologics were associated with serious viral infections related to EBV, CMV, VZV and HSV infection. 5 A meta-analysis of clinical trial data including 4135 patients given anti-tumour necrosis factor (TNF) therapy found that the relative risk of developing an opportunistic infection, including severe viral infections, was significantly increased in the anti-TNF arm. 30 33 Therefore, given the lack of effectiveness and possible harm, routine corticosteroids should be avoided unless they are indicated for another reason, according to WHO interim guidance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In a large study, thiopurines but not biologics were associated with serious viral infections related to EBV, CMV, VZV and HSV infection. 5 A meta-analysis of clinical trial data including 4135 patients given anti-tumour necrosis factor (TNF) therapy found that the relative risk of developing an opportunistic infection, including severe viral infections, was significantly increased in the anti-TNF arm. 30 33 Therefore, given the lack of effectiveness and possible harm, routine corticosteroids should be avoided unless they are indicated for another reason, according to WHO interim guidance.…”
Section: Discussionmentioning
confidence: 99%
“…These patients may have a greater risk of acquisition or progression of serious viral infections, including COVID-19. 5 However, the initial available evidence suggests that IBD patients do not have an increased risk of contracting SARS-CoV-2 infection or development of COVID-19, since no patients have been reported to be infected with SARS-CoV-2 in IBD centres in China. 6 Moreover, a recent study reported that none of the patients with IBD followed at a tertiary referral centre in Italy developed To date, there are limited data on patients with IBD who have had COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…However, a study in a tertiary care population of 2,600 patients with IBD followed for >15,000 patient-years described an exhaustive characterization and validation (hospitalization reports) of all serious viral infections (for example, all that required hospitalization) including varicella zoster virus (VZV), herpes simplex virus (HSV), cytomegalovirus (CMV) and Epstein-Barr virus (EBV) but not SARS-CoV-2 (ref. 7 ). The follow-up included >3,800 patient-years of exposure Management of IBD during the COVID-19 outbreak: resetting clinical priorities Silvio Danese 1,2 ✉ , Maurizio Cecconi 2,3 and Antonino Spinelli 2,4 The coronavirus disease (COVID-19) worldwide outbreak has led to a dramatic challenge for all healthcare systems, including inflammatory bowel disease (IBD) centres.…”
Section: Patients With Ibdmentioning
confidence: 99%
“…Previous studies have demonstrated that clinically active IBD and exposure to thiopurines increase the risk of viral infections (16,17). However, unlike other viruses (Influenza, Herpes, Cytomegalovirus, Adenovirus, Rhinovirus, Norovirus, and Respiratory Syncytial Virus), coronaviruses have not been shown to cause more severe disease in immunosuppressed patients (13,15,17).…”
Section: ' Introductionmentioning
confidence: 99%